Notice of Coins of David I. of Scotland, and Henry I. of England, found, with Gold Ornaments, &c., at Plan, in the Island of Bute, in June 1863 (Proceedings of the Society of Antiquaries of Scotland, 1865)
A transcription of John Pollexfen's presentation to the Numismatic Society of London on the coins found on the Isle of Bute in 1863. In his presentation, he provides a catalogue of the coins and analyses the quality and decoration of the collection. He also discusses the historical and numismatic significance of the coins found in Bute.